INCREASING THE SERVICE QUALITY FOR CUSTOMER SATISFACTION - Achmad Daengs GS; Mahjudin Mahjudin; Mashudah Hufron (Journal of Economics, Business, and Accountancy Ventura, 2012)
Business competition is unavoidable nowadays, whether it is either product or service, it has alwaysits own strategy to win. In this condition, service is the most important factor that should bebuilt and delivered to the customers. For that reason, service has to be qualified. This is due tothe fact that with qualified service, the customers will also be satisfied and then they will not thebusiness. A qualified service is marked by the number of consumers who were satisfied totallywith the service. So, every business must focus on it. PT. TIKI Branch of Kedung Sari Surabayawas the object of the research because service quality was critical. Theoretically, there are fivedimensions of service quality such as assurance, tangibles, reliability, responsiveness, and empathythat may influence customer satisfaction. The objective of this study was, to determine theeffect of service quality to customer satisfaction. Structural Equation Modeling (SEM) was usedto analyze the primer and secondary data during the research. With the probability of > 0.10, itwas found that assurance dimension could establish unidimensionality of service quality, whiletangibles, reliability, responsiveness, and empathy dimensions could not. Therefore, it could beconcluded that assurance was the prominent factor that caused customers satisfaction.